Evaluation Of Revenue Recognition Method Construction Contract PT. Wahana Multitron - Nicholas Nicholas; Syaiful Syaiful (PT. Publikasiku Academic Solution, 2023)
Background: The completed contract method is a method that recognizes the company's revenue and gross profit only when the contract or work is completed. Contract revenue is recognized only to the extent that the costs incurred are expected to be recovered. After all expenses are recognized, profit is recognized. Aim: The purpose of the study was to evaluate the method of recognizing revenue for construction contracts at PT. Wahana Multitron whether the revenue recognition method used was in accordance with accounting standards and to find out when and how revenue from construction services was recognized. The purpose of the study was to evaluate the method of recognizing revenue for construction contracts at PT. Wahana Multitron whether the revenue recognition method used was in accordance with accounting standards and to find out when and how revenue from construction services was recognized. Method: The research was conducted by evaluating the parts related to construction income, project costs, receipt of payment terms according to the construction contract agreement and the completeness of the supporting letters in carrying out the project. Findings:. The results of this study indicate that the company already has advantages such as a clear organizational structure and job description, systematic cost allocation. However, there are still some weaknesses such as errors in when to recognize construction revenue and errors in when to recognize project costs.